B Cell Functions Can Be Modulated by Antimicrobial Peptides in Rainbow Trout Oncorhynchus mykiss: Novel Insights into the Innate Nature of B Cells in Fish - Zhang, Xu-Jie; Wang, Peng; Zhang, Nu; Chen, Dan-Dan; Nie, Pin; Li, Jia-Le; Zhang, Yong-An (Frontiers in Immunology, 2017)
B cells in fish were recently proven to have potent innate immune activities like macrophages. This inspired us to further explore the innate nature of B cells in fish. Moreover, antimicrobial peptides (AMPs) are representative molecules of innate immunity, and they can modulate the functions of macrophages. These make fish an appropriate model to study the interactions between B cells and AMPs. Interestingly, the results in this study revealed that the IgM+ and IgT+ B cells of rainbow trout could express multiple AMP genes, including four cathelicidin genes and one β-defensin gene. The expression levels of the cathelicidin genes were obviously higher than that of the β-defensin gene. Further studies revealed that intracellular, extracellular, in vitro, and in vivo stimulations could significantly increase the expression of the cathelicidin genes in trout IgM+ and IgT+ B cells but not the expression of the β-defensin gene, indicating that cathelicidin peptides are the main innate immune effectors of trout B cells. More interestingly, we found that cathelicidin peptides could significantly enhance the phagocytic, intracellular bactericidal, and reactive oxygen species (ROS) activities of trout IgM+ and IgT+ B cells, a phenomenon previously reported only in macrophages, and these activities might also be mediated by the P2X7 receptor (P2X7R). These results collectively suggest that B cells play multiple roles in the innate immunity of fish, and they provide new evidence for understanding the close relationship between B cells and macrophages in vertebrates.